The Virgin Mary in the Temple of Justice: on how U.S. Jurisprudence is Messing up Argentine Constitutional Principles - Legarre, Santiago (2014)
This paper will illustrate how US constitutional law on the ?Establishment Clause? of the First Amendment to the Constitution of the United States2 is improperly influencing the religious culture and practices of Argentina. It will do so through the example of a dramatic real life situation which led to a momentous judicial decision. While drawing some conclusions from the affair, the paper will briefly consider the relevance of comparative constitutional analysis in the area of law and religion. It will also offer some observations on the comparative enterprise in general in order to attempt to explain how a problematic example, such as the Argentine case of the Virgin Mary in the Palace of Justice, can illuminate the proper understanding of comparative constitutional law.